THE CONCEPT OF COST BEHAVIOR IN MANUFACTURING COMPENIES - Muhammad Hamizan; Rifqi Ananda; Mahmud Kholil Shofa Siagian; Isra Hayati (Proceeding International Seminar of Islamic Studies, 2023)
This study examines the concept of cost behavior in Manufacturing Companies. The concept of cost behavior is very important for manufacturing companies to be able to make decisions about pricing, production, and other important aspects of the operations of the company. The method used is the literature review method. The results of this study indicate that companies adopting JIT or EMS systems may be experiencing a shift in cost behavior from fixed costs to variable costs, which can provide greater flexibility in responding to market demands and regulatory requirements. In extension, the study reveals that direct labor and material costs are mostly variable, while overhead costs are mostly fixed. This knowledge helps managers to better allocate costs and plan for changes in production. Overall, the literature provides valuable insights into how cost behavior can be managed to optimize business performance in manufacturing establishments.